Kemampuan Mengajar Santriwati pada Program ‘Amaliyah Tadris Pondok Pesantren Darul Amien Tarbiyatul Mu’allimin wal Mu’allimat Al-Islamiyah Teluk Labak - Fahrinawati (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2023)
This research is to determine the teaching abilities of female students in the implementation of the 'amaliyah tadris program at Darul Amien TMI Islamic Boarding School. In detail, the ability to carry out learning according to process standards includes initial activities, core activities, and closing activities. This research is a field research. The approach used is a qualitative approach with descriptive qualitative methods. This research founds that female students were able to open lessons by attracting students' attention, giving apperceptions, giving pretests and conveying learning objectives. Santriwati was able to close the lesson by reviewing the core material and giving a post test. Santriwati is able to apply skills in explaining, skills in asking questions, skills in giving reinforcement, and skills in carrying out variations during the learning process, although not all aspects of these components are applied.